Reform of power system governance in the context of system change. Issue 1 (20th April 2018) - Wright, Andrew C.
Abstract : Regulatory, commercial and governance arrangements form an integral part of any power system. They ensure that the underlying physical system fulfils the critical public function of electricity supply within agreed social and environmental constraints. If either the physical system or societal expectations change, the regulatory, commercial and institutional framework will need to adapt in response. This is necessary to ensure continued good outcomes for consumers at a reasonable cost. Power systems in many countries are going through rapid and substantial change, as a result of the twin pressures of decarbonisation and technological innovation. The power system is moving from one dominated by large‐scale, transmission‐connected, flexible thermal power stations serving passive demand, to an integrated smart system connecting increasingly distributed and intermittent energy resources integrated with an active demand side. As a result, there is a need for far‐reaching reforms of institutions, charging arrangements, market structures and regulations. Fundamental notions, such as security of supply and the universal service obligation need to be revisited. This is a challenge for policy makers and regulators wherever these changes are taking place.